2022
DOI: 10.1038/s41598-022-14233-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nitrogen species mixed with Ar and H2S plasma for directly N-doped TMD films synthesis

Abstract: Among the transition metal dichalcogenides (TMD), tungsten disulfide (WS2) and molybdenum disulfide (MoS2) are promising sulfides for replacing noble metals in the hydrogen evolution reaction (HER) owing to their abundance and good catalytic activity. However, the catalytic activity is derived from the edge sites of WS2 and MoS2, while their basal planes are inert. We propose a novel process for N-doped TMD synthesis for advanced HER using N2 + Ar + H2S plasma. The high ionization energy of Ar gas enabled nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Three typical peaks at 337, 316, and 358 nm are observed, corresponding to reactive N 2 * . [ 47 ] Few other peaks are found during 300 s nitridation based on both plasma strategies, verifying the existence of a highly purified nitriding environment without volatile Ni species. According to the nitridation process in p‐Ni 3 N, the peak intensity at 337 nm is continuously enhanced with elongated time, and comparatively the same peak regarding cp‐Ni 3 N exhibits little fluctuation (Figure 5c).…”
Section: Resultsmentioning
confidence: 86%
“…Three typical peaks at 337, 316, and 358 nm are observed, corresponding to reactive N 2 * . [ 47 ] Few other peaks are found during 300 s nitridation based on both plasma strategies, verifying the existence of a highly purified nitriding environment without volatile Ni species. According to the nitridation process in p‐Ni 3 N, the peak intensity at 337 nm is continuously enhanced with elongated time, and comparatively the same peak regarding cp‐Ni 3 N exhibits little fluctuation (Figure 5c).…”
Section: Resultsmentioning
confidence: 86%
“…So far, the application of photocatalysis technology is still only in laboratory-scale research, and the application of the actual industrial equipment is faced with significant technical barriers, which limits the application of photocatalysis technology [129][130][131][132]. Therefore, in the following research, it is urgent to carry out research continuously strengthening the understanding of the theories related to photocatalysis, such as the development of more advanced material preparation methods and characterization technology [133][134][135]; to strengthen interdisciplinary ideas and further explore photocatalytic technology in the process of integrating with different disciplines; develop new catalysts that are efficient, stable, safe, economical, and green, and suitable for industrial hydrogen production [136,137].…”
Section: Discussionmentioning
confidence: 99%
“…487 It has been shown that niobium doping gradually improves the gas sensitivity and stability of MoSe 2 up to 8% at 3 ppm NO 2 concentration. In another study conducted by Cho et al 488 nitrogen-doped MoS 2 and WS 2 thin films were synthesized by in situ doping during plasma assisted selenization of already-deposited transition metal films. It was found that the addition of Ar gas to a N 2 /H 2 S gas mixture enhances the nitrogen doping up to 8.3 and 9.43 at% in WS 2 and MoS 2 , respectively.…”
Section: In-situ Dopingmentioning
confidence: 99%